(untitled) (Research, Society and Development, 2023)
Objective: To identify didactic strategies for teaching electrocardiograms to undergraduate nursing students Method: integrative review of timeless studies published in the MEDLINE, Lilacs, Embase, Scopus, Cinahl and Web of Science databases. The search was carried out in June 2022, using controlled descriptors included in the Health Sciences Descriptors. The analysis was constructed from the processes of this review. Results: 13 original articles were characterized in terms of journal, year of publication, methodological design, which were categorized into three groups: 1-teaching methodology for electrocardiogram interpretation, 2-teaching method for performing electrocardiograms, and 3-development of didactic material for teaching electrocardiogram interpretation. Conclusion: it is considered that given the complexity of the electrocardiogram, its teaching should involve strategies to promote student qualification aimed at training professionals trained in the interpretation of the electrocardiogram. There is a need to discuss and reflect on the ways of teaching and learning the interpretation of the electrocardiogram in nursing courses.